Narrated Photography: visual representations of the sacred among young Polish migrants in England. (17th March 2015) - Dunlop, Sarah; Ward, Pete
Abstract : This article describes how a recently refined visual ethnographic research method, "narrated photography, " contributes to the study of religion. We argue that this qualitative research method is particularly useful for studies of lived religion and demonstrate this through examples drawn from a study the sacred among young Polish migrants to England. Narrated photography, which entails asking people to photograph what is personally significant to them and then to narrate the image, generates visual and textual material that mediates the subjective. Through using this method we discovered that family was considered to be sacred, both in terms of links to religious practice and a desire for a secure home which family relationships provide. Additionally, narrated photography has the potential to expand our conceptions of lived religion through the inclusion of visual material culture and the visual context of the research participants. In this case the data revealed that the Polish young people view structures within their landscape through a particularly Polish Catholic lens. These findings shed light on the religious tensions that migrants encounter in everyday life.